2.1 GHz electromagnetic field does not change contractility and intracellular Ca2+ transients but decreases β-adrenergic responsiveness through nitric oxide signaling in rat ventricular myocytes. (3rd October 2015) - Olgar, Yusuf; Hidisoglu, Enis; Celen, Murat Cenk; Yamasan, Bilge Eren; Yargicoglu, Piraye; Ozdemir, Semir
Abstract : Purpose : Due to the increasing use of wireless technology in developing countries, particularly mobile phones, the influence of electromagnetic fields (EMF) on biologic systems has become the subject of an intense debate. Therefore, in this study we investigated the effect of 2.1 GHz EMF on contractility and beta-adrenergic (β-AR) responsiveness of ventricular myocytes. Materials and methods : Rats were randomized to the following groups: Sham rats (SHAM) and rats exposed to 2.1 GHz EMF for 2 h/day for 10 weeks (EM-10). Sarcomere shortening and Ca 2+ transients were recorded in isolated myocytes loaded with Fura2-AM and electrically stimulated at 1 Hz, while L-type Ca 2+ currents (ICaL ) were measured using whole-cell patch clamping at 36 ± 1°C. Cardiac nitric oxide (NO) levels were measured in tissue samples using a colorimetric assay kit. Results : Fractional shortening and amplitude of the matched Ca 2+ transients were not changed in EM-10 rats. Although the isoproterenol-induced (10 −6 M) ICaL response was reduced in rats exposed to EMF, basal ICaL density in myocytes was similar between the two groups ( p < 0.01). Moreover, EMF exposure led to a significant increase in nitric oxide levels in rat heart ( p < 0.02). Conclusions : Long-term exposure to 2.1 GHz EMF decreases β-AR responsiveness of ventricular myocytes through NO signaling.